MENYINGKAP PERSPEKTIF TUNGGAL DALAM KOMUNIKASI BENCANA ERUPSI GUNUNG SINABUNG MELALUI DETIK.COM - Puji Lestari; Harnum Ayu Rinasti (Universitas Bunda Mulia, 2020)
This study aims to analyze the tendency of online media coverage detik.com August-September 2017 period about the eruption of Mount Sinabung disaster communication. Social responsibility theory and disaster journalism are used as reference analysis. This research uses a quantitative content analysis method with documentation of data collection techniques and literature study. The validity test of the data used in this study is the reliability test. The results of this study found that news about the eruption of Mount Sinabung on Detik.com tended to be informative based on the type of news was dominated by straight news, the news length was 6-10 paragraphs, there was the use of the word